2020
DOI: 10.1007/s11292-020-09418-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical change in psychopathic traits after the PSYCHOPATHY.COMP program: preliminary findings of a controlled trial with male detained youth

Abstract: On behalf of my co-authors and myself, I would like to thank your comments and those of the reviewers, resulting from a careful reading and review of our paper, "Clinical change in psychopathic traits after an individual compassion focused therapy-based intervention:Preliminary findings of a controlled trial with male detained youth" (JOEX-D-19-00063), which now reads "Clinical change in psychopathic traits after the PSYCHOPATHY.COMP program:Preliminary findings of a controlled trial with male detained youth" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 64 publications
5
41
0
Order By: Relevance
“…These findings indicate that the strategy of change of the PSYCHOPATHY.COMP program was effective in reducing CU traits, which go against a substantial amount of research suggesting that CU traits may be particularly resistant to treatment efforts (Butler et al, 2011;Wilkinson et al, 2015). If these findings prove to be consistent in future studies, this may indicate that specific and tailored interventions, such as the PSYCHOPATHY.COMP program, can be effective in decreasing this set of traits (Ribeiro da Silva et al, 2020b).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These findings indicate that the strategy of change of the PSYCHOPATHY.COMP program was effective in reducing CU traits, which go against a substantial amount of research suggesting that CU traits may be particularly resistant to treatment efforts (Butler et al, 2011;Wilkinson et al, 2015). If these findings prove to be consistent in future studies, this may indicate that specific and tailored interventions, such as the PSYCHOPATHY.COMP program, can be effective in decreasing this set of traits (Ribeiro da Silva et al, 2020b).…”
Section: Discussionmentioning
confidence: 82%
“…The PSYCHOPATHY.COMP program is the first CFT-based program specifically designed to target psychopathic traits among detained youth. Although preliminary studies showed that this program was effective in reducing psychopathic traits in this at-risk population, the study's methodological weaknesses (e.g., small sample size, lack of follow-up assessment) warranted caution when interpreting its results (Ribeiro da Silva et al, 2020b). This controlled trial tried to overcome these shortcomings by testing the efficacy of this program in reducing psychopathic traits in a larger sample of male detained youth and by testing if those effects were maintained six months after the PSYCHOPATHY.COMP completion.…”
Section: Discussionmentioning
confidence: 99%
“…In many ways, because these are individuals that often manipulate themselves into power, these are the individuals for whom we need to find ways of engaging them with and supporting compassion training. Nonetheless some inspiring work developing CFT in forensic populations have shown that it may l have potential to reduce psychopathic traits in some people (da Silva et al, 2020).…”
Section: Contextualizing Compassionmentioning
confidence: 99%
“…The growing empirical support of CFT (see Leaviss & Uttley, 2015 for a review), the reliability of conceptual models explaining psychopathic traits under the lens of a CFT approach (Ribeiro da Silva, Vagos, & Rijo, 2019), and the compelling theoretical support of CFT as an adequate treatment for youth with disruptive behavior and psychopathic traits (Ribeiro da Silva et al, 2013, 2015) lead Ribeiro da Silva et al (2017) to develop the PSYCHOPATHY.COMP program: an individual compassion-based psychotherapeutic intervention for juvenile detainees with CD and psychopathic traits. The main goal of this program is to reduce psychopathic traits and disruptive behavior through the development of a compassionate motivation in these youth, toward both the self and others.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%